The relationship between observed and perceived assessments of the coach-created motivational environment and links to athlete motivation. (March 2016) - Smith, N.; Tessier, D.; Tzioumakis, Y.; Fabra, P.; Quested, E.; Appleton, P.; Sarrazin, P.; Papaioannou, A.; Balaguer, I.; Duda, J.L.
Abstract: Objectives: The majority of research examining the relationship between the coach-created motivational and athlete motivation has relied on self-report measures. Grounded in Duda's (2013) theoretically integrated model, the present study examined: (1) athletes', coaches' and observers' reports of the multidimensional motivational coaching environment in four European countries, (2) the interrelationships of these different perspectives of the motivational environment, and (3) links between the multidimensional environment and athletes' autonomous, controlled and amotivation. Design: We employed a cross-sectional study design and utilized mixed methods to tap the variables of interest. Both descriptive and more sophisticated multi-level statistical analyses were employed to test our hypotheses. Methods: Seventy-four grassroots soccer coaches and 882 youth athletes from England, France, Greece and Spain were recruited. Coaches were video-recorded during a training session and observers rated the degree to which the coaching climate was autonomy supportive, controlling, task-involving, ego-involving and relatedness supportive. Athletes and coaches completed questionnaires assessing their perceptions of the coach created climate in relation to the aforementioned dimensions of the environment. Athletes also completed measure of their sport-based motivation regulations. Results: A profile of the motivational environment and athlete motivation was presented actoss four countries. There were weak associations found between different perspectives of the multidimensional coaching environment. However, athletes', coaches' and observers' reports of features of the motivational environment emerged as significant predictors of athletes' autonomous, controlled and amotivation. Conclusions: Results provide partial support for findings of previous studies examining athlete motivation correlates of the motivational environment relying solely on self-report measures. Findings also point to the value of adopting a mixed-methodological approach and including athletes', coaches' and observers' reports of the environment when time and resources allow. Highlights: Mixed-method multi-country study of coaching and motivation. Profile of empowering and disempowering motivational climate. Limited agreement between observed and athlete-perceived environment. Observed reports predictive of athlete motivation. Implications for future research on motivation and coaching in sport.